A Meta-Synthesis Analysis of the Use of Audio-Visual Media in Early Childhood Language Learning: A Comparative Study - Anggraini, Wardah (Madiha Press, 2025)
This meta-synthesis systematically investigates the dual impact of audio-visual media on early childhood language development, drawing from 100 studies published over the last 10-15 years. The research analyzes existing literature to identify general patterns of both positive and negative effects. Findings consistently show that high-quality, age-appropriate audio-visual content, particularly when accompanied by active adult mediation, significantly enhances vocabulary acquisition, narrative comprehension, and learning motivation. Conversely, excessive or passive media consumption without interaction poses considerable risks, including potential speech delays, attention span issues, and reduced social interaction. This study concludes that audio-visual media can be a valuable supplementary tool if used thoughtfully and responsibly. Its impact is highly contingent on content quality, duration, and the presence of adult guidance, emphasizing the critical need for informed practices among educators and parents.